2021
DOI: 10.3390/polym13172885
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Co-Transport of Carboxylate Ions and Ethanol in Anion Exchange Membranes

Abstract: Understanding multi-component transport behavior through hydrated dense membranes is of interest for numerous applications. For the particular case of photoelectrochemical CO2 reduction cells, it is important to understand the multi-component transport behavior of CO2 electrochemical reduction products including mobile formate, acetate and ethanol in the ion exchange membranes as one role of the membrane in these devices is to minimize the permeation of these products. Anion exchange membranes (AEM) have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…While diffusion of H 2(aq) is slower across thicker membranes, ion flux will also be proportionally depressed. The free volume model works reasonably well for neutral solutes with relatively high molecule weights and high swelling degree IEMs, suggesting that the permeants indeed transport through the solvated fraction of the membranes (Yasuda et al, 1969;Kato et al, 1992;Dischinger et al, 2020;Kim and Beckingham, 2021;Kim et al, 2021a;Kim et al, 2022a). However, for smaller solutes, such as H 2(aq) , and low swelling degree membranes, the permeant can plausibly be transported through the unsolvated free volumes within the polymer chains, akin to gas permeation across dense films (Baker, 2012).…”
Section: Ion/uncharged Solute Selectivitymentioning
confidence: 99%
“…While diffusion of H 2(aq) is slower across thicker membranes, ion flux will also be proportionally depressed. The free volume model works reasonably well for neutral solutes with relatively high molecule weights and high swelling degree IEMs, suggesting that the permeants indeed transport through the solvated fraction of the membranes (Yasuda et al, 1969;Kato et al, 1992;Dischinger et al, 2020;Kim and Beckingham, 2021;Kim et al, 2021a;Kim et al, 2022a). However, for smaller solutes, such as H 2(aq) , and low swelling degree membranes, the permeant can plausibly be transported through the unsolvated free volumes within the polymer chains, akin to gas permeation across dense films (Baker, 2012).…”
Section: Ion/uncharged Solute Selectivitymentioning
confidence: 99%
“…As a conjecture, mobile formate anions (OFm – ) may be more favorable in QA + -containing films (counterion condensation , ). In mixed solute sorption, OFm – mobility can be reduced in these films as MeOH softens the fixed charge interface and interferes with the counterion condensation. , …”
Section: Resultsmentioning
confidence: 99%
“…These relative permeabilities are attributed to the differences in solute size, kinetic diameter for the alcohols, and hydrated diameter for the carboxylate salts. The kinetic diameter of EtOH (4.5 Å [ 33 ]) is higher than the kinetic diameter of MeOH (3.6 Å [ 34 ]), and the hydrated diameter of OFm − (5.9 Å [ 35 ]) is smaller than the hydrated diameter of OAc − (7.44 Å [ 32 , 36 ]). The smaller solutes permeate faster than the larger solutes (diffusivity varies inversely proportional to the solute size).…”
Section: Resultsmentioning
confidence: 99%
“…However, at higher pre−polymerization water content, and thereby higher water volume fraction, EtOH permeability decreases in co-permeation with NaOAc. Recently, in a study by Kim et al (2021) , it was observed that EtOH permeability remained essentially the same in PEGDA-based films in single and co-transport with carboxylate ions, which was attributed to the larger observed differences in sorption behavior of EtOH for these mixtures (ethanol’s solubility was 0.298 whereas the solubility was 0.386 while co-transporting with NaOFm) [ 34 ]. Thus, in our current study, the consistency in permeability values for EtOH between single and co-permeation in PEGDA-PEGMA films with NaOFm is likely also a result of analogous sorption differences that might compensate for the difference in the diffusive behavior between two molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation